Digital microfabrication of user‐defined 3D microstructures in cell‐laden hydrogels. Issue 11 (3rd June 2013) - Soman, Pranav; Chung, Peter H.; Zhang, A. Ping; Chen, Shaochen
ABSTRACT Complex 3D interfacial arrangements of cells are found in several in vivo biosystems such as blood vasculature, renal glomeruli, and intestinal villi. Current tissue engineering techniques fail to develop suitable 3D microenvironments to evaluate the concurrent effects of complex topography and cell encapsulation. There is a need to develop new fabrication approaches that control cell density and distribution within complex 3D features. In this work, we present a dynamic projection printing process that allows rapid construction of complex 3D structures using custom‐defined computer‐aided‐design (CAD) files. Gelatin‐methacrylate (GelMA) constructs featuring user‐defined spiral, pyramid, flower, and dome micro‐geometries were fabricated with and without encapsulated cells. Encapsulated cells demonstrate good cell viability across all geometries both on the scaffold surface and internal to the structures. Cells respond to geometric cues individually as well as collectively throughout the larger‐scale patterns. Time‐lapse observations also reveal the dynamic nature of mechanical interactions between cells and micro‐geometry. When compared to conventional cell‐seeding, cell encapsulation within complex 3D patterned scaffolds provides long‐term control over proliferation, cell morphology, and geometric guidance. Overall, this biofabrication technique offers a flexible platform to evaluate cell interactions with complex 3D micro‐features, with the ability to scale‐up towards high‐throughput screening platforms. Biotechnol. Bioeng. 2013;110: 3038–3047. © 2013 Wiley Periodicals, Inc.